Investor Sentiment and Stock Price Dynamics in the Banking Sector: An Analysis of Indonesia’s Government Transition Period 2024-2025 - Permatasari, Adinda Putri; Habiburrochman, Habiburrochman; Putri, Elma Nazila (Amkop Management Accounting Review (AMAR), 2026)
This study examines the stock market reaction of the banking sector to Indonesia’s government transition in 2024-2025 by focusing on investor sentiment. An event study approach using daily time series data is employed, with the financial sector index (IDXFINANCE) listed on the Indonesia Stock Exchange as the research object. The inauguration of the President and Vice President of the Republic of Indonesia on October 20, 2024, is designated as the event date (t = 0), with an event window of −10 to +10 trading days. Market reactions are measured using abnormal return (AR) and cumulative abnormal return (CAR), and their significance is tested using a one-sample t-test. The results show that abnormal returns in the pre-event, event, and post-event periods are not statistically significant, indicating no strong short-term market reaction. In contrast, cumulative abnormal return is negative and statistically significant both before and after the event date. These findings suggest that investor sentiment during the government transition accumulates gradually and exerts negative pressure on the performance of banking-sector stocks. Overall, the results are consistent with behavioral finance, investor sentiment, and herding behavior theories, highlighting the greater impact of political uncertainty on cumulative stock price movements rather than daily reactions.